Modified epoxy matrix with improved properties for protection of transport vehicles - Brailo, M.V.; Bezbakh, O.M.; Husiev, V.M.; Yakushchenko, S.V. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
It is substantiated that for improving the performance characteristics of vehicle parts, including their corrosion and wear resistance, it is advisable to use protective polymeric composite coatings. It is shown that in order to increase the indexes of physical and mechanical and thermophysical properties in the epoxy binder, it is necessary to introduce additives: modifiers, plasticizers, dispersed and fiber fillers. The introduction of modifiers into the epoxy binder is relevant, and effectively use them in the complex. The influence of modifier and hardener on the adhesion strength and destructive stresses during bending of the developed epoxy composite has been analyzed. The critical content of the components: the MBMA modifier is 0.25 . . . 0.50 pts.wt., hardener PEPA — 8 . . . 10 wt. per 100 pts.wt. of epoxy oligomer ED-20 was found by the method of mathematical planning of the experiment. The introduction of such ingredients into the epoxy binder increases the adhesion strength of matrix to σa = 28.9 . . . 31.3 MPa and the fracture stresses during the flexion to σf l = 51.2 . . . 54.4 MPa. The obtained results allow to create materials with improved physical and mechanical properties in the complex.
Көлiк құралдарын қорғау үшiн жақсартылған қасиеттерi бар модификацияланған эпоксидтi матрица
Модифицированная эпоксидная матрица с улучшенными свойствами для защиты транспортных средств
Keywords: composite; epoxy matrix; method of mathematical planning of the experiment; regression equation